Organic anion transporting polypeptide 1B3 can form homo- and hetero-oligomers. - Yuchen Zhang; Kelli H Boxberger; Bruno Hagenbuch (PLoS ONE)
OATP1B3 is a 12 transmembrane domain protein expressed at the basolateral membrane of human hepatocytes where it mediates the uptake of numerous drugs and endogenous compounds. Previous western blot results suggest the formation of OATP1B3 multimers. In order to better understand the function of OATP1B3 under normal physiological conditions, we investigated its oligomerization status. We transiently transfected OATP1B3 with a C-terminal His-, FLAG- or HA-tag in HEK293 cells and used co-immunoprecipitation and a Proximity Ligation Assay to detect interactions between the different constructs. All three constructs retained similar transport rates as wild-type OATP1B3. Immunofluorescence experiments indicated that in contrast to wild-type, His- and FLAG-tagged OATP1B3, where the C-terminal end is on the cytoplasmic side of the membrane, the C-terminal end of HA-tagged OATP1B3 is extracellular. After cross-linking, anti-FLAG antibodies were able to pull down FLAG-tagged OATP1B3 (positive control) and co-transfected His- or HA-tagged OATP1B3, demonstrating the formation of homo-oligomers and suggesting that the C-terminal part is not involved in oligomer formation. We confirmed co-localization of His- and FLAG-tagged OATP1B3 in transfected HEK293 cells with the Proximity Ligation Assay. Transport studies with a non-functional OATP1B3 mutant suggest that the individual subunits and not the whole oligomer are the functional units in the homo-oligomers. In addition, we also detected OATP1B3-FLAG co-localization with OATP1B1-His or NTCP-His, suggesting that OATP1B3 also hetero-oligomerizes with other transport proteins. Using the Proximity Ligation Assay with transporter specific antibodies, we demonstrate close association of OATP1B3 with NTCP in frozen human liver tissue. These findings demonstrate that OATP1B3 can form homo- and hetero-oligomers and suggest a potential co-regulation of the involved transporters.